The French Reception of Husserl: Between Existence and Knowledge - Hernandez Marcelo, Jimmy (Disputatio, 2023)
This study aims to describe the process of reception and assimilation of Husserlian phenomenology in France, articulated in two parallel traditions, namely the philosophy of subject and the philosophy of concept. The former is linked to the interpretation of Levinas-Sartre and the latter to the epistemological heritage of Koyré-Cavaillès. Finally, we briefly present the critical trace of Cavaillès in certain authors directly or indirectly related to his critique of phenomenology (Tran Duc Thao, S. Bachelard and Derrida).